Role of Single Low Pulse Intensity of Transcranial Magnetic Stimulation Over the Frontal Cortex for Cognitive Function - Bashir, Shahid; Al-Hussain, Fawaz; Hamza, Ali; Shareefi, Ghadah Faisal; Abualait, Turki; Yoo, Woo-Kyoung (Frontiers in Human Neuroscience, 2020)
Background: The principal aim of this study was to measure the effect of online single-pulse transcranial magnetic stimulation (TMS) over the right dorsolateral prefrontal cortex (DLPFC) on cognition via the Cambridge Neuropsychological Test Automated Battery (CANTAB) in healthy individuals. Methods: In a single-blinded, sham-controlled study, we assessed both 50% and 60% of the resting motor threshold (RMT) over the right DLPFC in healthy right-handed (n = 42) adults using cognitive function, such as attention and memory, as a measure via CANTAB. Results: We observed an improvement in cognitive function level during the use of online low intensities of 50% and 60% RMT active stimulation of the DLPFC compared to the sham stimulation. Conclusions: The results reflected significant differences in cognitive function for the factor location of the TMS and an interaction effect for intensity and location. This study showed that the lowest intensity TMS can indeed effectively modulate neural activation.